The fracture properties of fiber metal laminates based on a 3D printed glass fiber composite. (February 2023) - Yelamanchi, B; MacDonald, E; Gonzalez-Canche, NG; Carrillo, JG; Cortes, P
Fiber Metal Laminates (FML) are structures that contain a sequential arrangement of metal and composite materials, which are of great interest to the aerospace sector due to the superior mechanical performance. The traditional manufacturing process for FML involves considerable investment in manufacturing resources depending on the design complexity of the desired components. To mitigate such limitations, 3D printing enables direct digital manufacturing to create FML with customized configurations. In this work, a preliminary mechanical characterization of additively-manufacturing-enabled FML has been investigated. A series of continuous glass fiber-reinforced composites were printed with a Markforged system and placed between layers of aluminum alloy to manufacture hybrid laminate structures. The laminates were subjected to tensile, interfacial fracture toughness, and both low-velocity and high-velocity impact tests. The results showed that the FMLs appear to have a good degree of adhesion at the metal-composite interface, although a limited intralaminar performance was recorded. It was also observed that the low and high-velocity impact performance of the FMLs was improved by 9–13% relative to that of the constituent elements. The impact performance of the FML appeared to be related to the fiber fracture, out of plane perforation and interfacial delamination within the laminates. The present study can provide an initial research foundation for considering 3D printing in the production of hybrid laminates for static and dynamic applications.